Nicotine addiction and smoking cessation strategies - Michael Kourakos; Theodora Kafkia; Evangelos Fradelos (Ene, 2016)
The use of tobacco was first reported in the 6th century BC, but the 20th century has been marked by the widespread use of tobacco and the establishment and expansion of large tobacco companies. The public health community did not address initially smoking as harmful and addictive, despite the fact that many other observers of human behavior (authors, psychologists, religious leaders) had stressed out its addictive characteristics. In the late 1980s, the acceptance of the addictive nature of tobacco resulted in development of healthcare services aiming at supporting people quit smoking and legislation regarding sale, distribution and advertising of tobacco products. Nicotine dependence is a chronic condition for which effective therapeutic interventions are required. Smokers, unlike other substances addicts, do not recognize their addiction and the nicotine withdrawal syndrome that they experience. For establishing the degree of dependence various tools can be used, such as the method of the 4 Cs (compulsion, control, cutting down, consequences) or validated questionnaires (CAGE, Fagerström Test for Nicotine). The main smoking cessation strategies use replacement therapy with various products (patch, gum, etc), medications (bupropion, varenicline) and/or counseling. These interventions are clinically efficient but also cost-effective, compared to prevention and treatment of diseases associated with smoking. Smoking cessation interventions should be offered to every smoker and provided by their health insurance.